Alkyl polyglycoside surfactant-alcohol cosolvent formulations for improved oil recovery - Iglauer, Stefan; Wu, Y.; Shuler, P.; Tang, Y.; Goddard, W. (Elsevier BV, 2009)
We examine here the suitability of alkyl polyglycosides (APG) for improved oil recovery (IOR) applications. In recent years, these nonionic carbohydrate-based surfactants have become a significant commercial product (80,000 tons/year) with widespread use in household and agricultural products. Our laboratory study determined several characteristics of common APG surfactant formulations, in particular their capability to create low interfacial tensions (IFT) with n-alkane hydrocarbons. Our formulations included a wide range of alcohol cosurfactants with APG surfactants. We found APG–cosurfactant combinations that exhibit low IFT values of 0.01 mN/m or less versus n-octane. Our laboratory tests confirmed these APG formulations can provide useful IFT properties that are largely independent of both salinity and temperature. We report a coreflood test conducted on a Berea sandstone core using a selected formulation that exhibits oil recovery as high as 85% IOIP.